IMPACT OF FISH AUCTION SITE WASTE ON GROUNDWATER POLLUTION LEVEL IN LAMPULO VILLAGE - Mice Putri Afriyani; Naurah Amalia; Muttakin Muttakin (GeoEco, 2026)
Waste generated from activities at the fish auction site in Lampulo Village has the potential to degrade environmental quality, particularly groundwater quality. This study aims to assess the impact of waste from fish auction sites on groundwater quality in Lampulo Village. Groundwater quality was evaluated using electrical conductivity (EC) and salinity parameters to indicate pollution levels. The results show that groundwater quality in the study area has significantly declined due to waste generated from fish auction activities. Groundwater pollution levels are classified as very high, with EC values exceeding 4,500 µS/cm, indicating very saline groundwater conditions. Electrical conductivity is the ability of groundwater to conduct an electric current and reflects the concentration of dissolved ions, which serves as an important indicator of groundwater contamination. Elevated EC values observed in Lampulo Village suggest a substantial contribution from dissolved salts originating from waste from the fish auction site. Furthermore, groundwater salinity classification reveals that most groundwater wells in the study area fall within the brackish and salty water categories. These conditions indicate that groundwater surrounding the fish auction site has been contaminated and is no longer suitable for domestic use, including drinking, cooking, and bathing. This study emphasises the need for effective waste management strategies at the fish auction site to mitigate groundwater pollution and to support environmental sustainability and public health protection in coastal settlement areas.